An empirical examination of self-reported work stress among U.S. managers. - Cavanaugh, Marcie A.; Boswell, Wendy R.; Roehling, Mark V.; Boudreau, John W. (Journal of Applied Psychology, 2000)
This study proposes that self-reported work stress among U.S. managers is differentially related (positively and negatively) to work outcomes depending on the stressors that are being evaluated. Specific hypotheses were derived from this general proposition and tested using a sample of 1,886 U.S. managers and longitudinal data. Regression results indicate that challenge-related self-reported stress is positively related to job satisfaction and negatively related to job search. In contrast, hindrance-related self-reported stress is negatively related to job satisfaction and positively related to job search and turnover. Future research directions are discussed.